Adaptability Study of Hot Water Chemical Flooding in Offshore Heavy Oilfields. (17th November 2022) - Zhang, Zenghua; Jin, Yi; Zhang, Jian; Tang, Engao; Wei, Zhijie; Liang, Dan; Li, Peihuan
Abstract : As a new heavy oil development technology, hot water chemistry flooding has great potential in offshore heavy oil fields development. In this paper, the adaptability of hot water chemical flooding was studied based on the typical model of offshore heavy oil fields. The main controlling factors affecting the hot water chemical flooding were analyzed and evaluated by single factor analysis. The technical boundary was established for offshore heavy oil fields. In addition, the hot water chemical flooding scheme was designed by a case study of a well group oilfield D. The results indicate that crude oil viscosity and well spacing have great influences on hot water chemical flooding performance. Hot water chemical flooding is favorable when the crude oil viscosity is between 300 and 1000 mPa·s and well spacing is around 200 400 m. The hot water chemical flooding scheme of the target well group results in 40.2 × 10 4 tons of incremental oil, and 6.3% of recovery factor being enhanced, which shows strong evidence that hot water chemical flooding enables great oilfield development performance.